Early Adjunctive Treatment with Human Cytomegaly Virus (CMV) Immunoglobulin Increased CMV-Free Survival after Heart Transplantation. (July 2018) - Neumaier, Carolin; Bernhardt, Alexander; Rybczynski, Meike; Plaetke, Rosemarie; Reichenspurner, Hermann; Barten, Markus J
Abstract : Introduction: There is still an ongoing discussion whether a prophylactic or a preemptive therapy against cytomegalovirus (CMV) is superior to reduce the incidence of CMV viremia, acute rejections (AR) and cardiac allograft vasculopathy (CAV) in the long-term after heart transplantation (HTx). Thus, in this study we evaluated different CMV treatmnent strategies in this setting. Materials and Methods: In this retrospective study we included 56 patients, who got a HTx between 1st of January 2010 and 31st of July 2016 at our center. Excluded were all patients who died within the first 90 days or who had a loss to follow-up in the first year after HTx. Study end points were the CMV-free survival viremia, AR, CAV and death. The patients were followed up for an average of 4.15 years (355 days up to 7.5 years). Patients were classified into 3 groups according to their received CMV-protocol: preemptive therapy (n=19), prophylactic mono drug therapy (either valganciclovir for average of 110 days or early single dose of 100mg/kg/BW of cytomegaly virus immunoglobulin, CMVIG, within the first two weeks post-HTx, n=18) or prophylactic double drug therapy (valganciclovir for 3 months plus early single dose of CMVIG, n=19). For statistical analysis X2, X2-log-rank and T-Tests were used. Results and Discussion: Overall seven patients of our study cohort died (unknown cause n=2, AR n=3, and sepsis n=2). The median patient survival post-HTx was not significant different among the study groups: preemptive group 2243 days, prophylactic monotherapy 2417 days, and prophylactic double therapy 2410 days, respectively (p=0.73). However, the median CMV-viremia free survival was different among the groups: 1817 days in the prophylactic double group, 1459 days in the prophylactic mono group and 1482 in the preemptive group (p=0.52). Especially, in a subanalysis patients with a high risk for CMV infection (donor positive and recipient negative CMV status, n=13) the CMV-free survival was significantly higher when patients received double prophylaxis therapy compared to the other two groups (p<0.01). Whether the incidence of AR nor of CAV was not significantly influenced by the choice of CMV treatment regimen (p=0.87 and p=0.215, respectively). Overall in 15 patients the antiviral medication was discontinuated due to side effects such as leukopenia, preemptive group 10.5%, prophylactic monogroup 38.9%, and prophylactic double group 31.6%, respectively. Conclusion: Our study results suggest that early therapy with CMVIG as adjunct to antiviral treatment could prolong CMV-free survival in patients with high risk of CMV infection. If a repetitive CMVIG dosing post-HTx will further reduce CMV infection needs to be explored in the future.